Keeping cost effectively warm: the inclusion of thermal performance in the New Zealand Building Code - Isaacs, Nigel (Architectural History Aotearoa, 2020)
The 1990s saw change from the (nominally) prescriptive NZS1900 to the performance-based New Zealand Building Code (NZBC). Although there had been thermal insulation requirements for new houses since 1 April 1978, the change provided the opportunity to develop a performance-based requirement. It also provided the opportunity to include non-residential buildings, notably including for the first-time office and retail buildings. While around two thirds of energy use in houses is for space conditioning (heating) and water heating, in commercial buildings the main energy uses are space conditioning (heating and cooling) and lighting. Extensive background research developed a set of proposed documents, which were then refined using the Committee structure of Standards New Zealand. The three standards (NZS 4218 Energy Efficiency: Housing and Small Building Envelope, NZS 4243 Energy Efficiency: Large Buildings and NZS 4305: Energy efficiency: Domestic type hot water systems) provided an integrated series of standards. The paper will explore the background research, the use of Standards Committees, and the political issues that played a crucial role in delaying the implementation.